COMPARATIVE ANALYSIS OF TREATMENT RESULTS IN PATIENTS WITH DAMAGE TO DUENUM IN DIFFERENT SURGICAL TACTICS - S.A. Ruziboev; Kh.R. Amonov (Central Asian Journal of Medicine, 2022)
The analysis of the results of surgical treatment and complications in the early postoperative period in 82 patients with duodenal lesions was carried out. The most frequent and formidable complication in the early postoperative period is the failure of the sutures of the duodenal wound with the development of peritonitis or the formation of an external fistula. The immediate complication leading to a fatal outcome is most often the failure of the sutures of the anastomoses to be applied, retroperitoneal phlegmon, which leads to septic infection and systemic multiple organ failure (SPON).